(untitled) (Al-Qamar, 2023)
Aesthetic is concerned with beauty or the appreciation of beauty. It is used to talk about beauty or art and people’s appreciation of beautiful things. Its value can be defined as sensation or feeling of enjoying beauty. Every human will have the value of aesthetics or aesthetic sense that one get to enjoy whatever he sees in his daily life. As a study it aims at the understanding of beauty that is prescribed in front of us. It is not just expressing, enjoying beauty our inner emotions are connected to pursuit of beauty in all its means. In this article Dr. Naseer Ahmad Nasir view on Aestheticism are described who is a notable Islamic Scholar & philosopher from Pakistan. He wrote numerous books on aesthetics including Husn- e -Tafseer in three volumes. His important contribution to philosophy was research on Aesthetics. He tries to explore the Holy Quran with reference of Philosophy of Aesthetics. He claims that it is a unique effort because his work is matchless throughout the Muslim World. Actually, aesthetic is successful attempt to view and to discover the beauty of universe. Human being is part of its beauty and Holy Quran invites this creature to create a very beautiful society to live in. He tries to put before the world this aspect of Holy Quran.